Inhibitions of late INa and CaMKII act synergistically to prevent ATX-II-induced atrial fibrillation in isolated rat right atria. (May 2016) - Liang, Faquan; Fan, Peidong; Jia, Jessie; Yang, Suya; Jiang, Zhan; Karpinski, Serge; Kornyeyev, Dmytro; Pagratis, Nikos; Belardinelli, Luiz; Yao, Lina
Abstract: Aims: Increases in late Na + current (late I Na) and activation of Ca 2 + /calmodulin-dependent protein kinase (CaMKII) are associated with atrial arrhythmias. CaMKII also phosphorylates Nav 1.5, further increasing late I Na . The combination of a CaMKII inhibitor with a late I Na inhibitor may be superior to each compound alone to suppress atrial arrhythmias. Therefore, we investigated the effect of a CaMKII inhibitor in combination with a late I Na inhibitor on anemone toxin II (ATX-II, a late I Na enhancer)-induced atrial arrhythmias. Methods and results: Rat right atrial tissue was isolated and preincubated with either the CaMKII inhibitor autocamtide-2-related inhibitory peptide (AIP), the late I Na inhibitor GS458967, or both, and then exposed to ATX-II. ATX-II increased diastolic tension and caused fibrillation of isolated right atrial tissue. AIP (0.3 μmol/L) and 0.1 μmol/L GS458967 alone inhibited ATX-II-induced arrhythmias by 20 ± 3% (mean ± SEM, n = 14) and 34 ± 5% (n = 13), respectively, whereas the two compounds in combination inhibited arrhythmias by 81 ± 4% (n = 10, p < 0.05, vs either AIP or GS458967 alone or the calculated sum of individual effects of both compounds). AIP and GS458967 also attenuated the ATX-induced increase of diastolic tension. Consistent with the mechanical and electrical data, 0.3 μmol/L AIP and 0.1 μmol/L GS458967 each inhibited ATX-II-induced CaMKII phosphorylation by 23 ± 3% and 32 ± 4%, whereas the combination of both compounds inhibited CaMKII phosphorylation completely. Conclusion: The effects of an enhanced late I Na to induce arrhythmic activity and activation of CaMKII in atria are attenuated synergistically by inhibitors of late I Na and CaMKII. Highlights: Combination of a CaMKII inhibitor with a late I Na inhibitor on AF was proposed. AIP and GS967 or ranolazine synergistically inhibited ATX-II-induced AF. AIP and GS967 synergistically inhibited ATX-II-induced increase of diastolic tension. AIP and GS967 completely attenuated ATX-II-induced CaMKII phosphorylation. These findings may have broad application to AF and ischemic heart disease.